Administrative Measures Against Far-Right Protesters: An Example of Japan's Social Control - Löschke, Ayaka (Social Science Japan Journal, 2021)
Japan's pre-emptive approach to far-right demonstrations has had a significant impact. Far-right street protests accompanied by hate speech have been rapidly decreasing, although Japan has not introduced penalties. Why did the Japanese approach have such an effect? While the regulation of hate speech in Japan has been discussed mainly in legal studies, Japan's use of administrative measures against hate speech has not been emphasized. Focusing on the implementation of the 2016 Hate Speech Law, this article examines administrative measures against far-right protestors as an example of Japan's 'soft' approach to social control: not directly banning but discouraging social activities that are deemed harmful to social harmony. These measures have a pre-emptive character and are implemented based on a prior consensus between local officials and far-right activists about appropriate ways to use public spaces and possible expressions. This article also shows that Japan's treatment of both far-right protesters and counterdemonstrators is guided by the harmony-related concept of kenka ryoseibai, which imposes punishment on both parties in a private quarrel, whether right or wrong. Japan's approach to far-right protests thereby differs from the conventional American and European approaches in terms of both forms of regulation and central values.
CRIS-Team WoS Importer:2022-02-04
Keywords: far-right protesters; hate speech; administrative guidance; social harmony

ANTINUCLEAR CITIZENS: Sustainability Policy and Grassroots Activism in Post-Fukushima Japan | By Akihiro Ogawa - Löschke, Ayaka (Pacific Affairs, 2024)

A victims’ movement against the termination of housing support for voluntary evacuees - Löschke, Ayaka (Japan Forum, 2021)
After the Fukushima nuclear disaster, more than 50,000 people moved from irradiated areas without being ordered to do so by the government. They are called ‘voluntary evacuees’. Because they received very little compensation, a government policy to provide rent-free public housing units has been a lifeline for about 25,000 voluntary evacuees. However, the housing support expired on 31 March 2017. Based on sixty semi-structured, problem-centred interviews, this article provides an analysis of the victims’ movement against the termination of the housing support. After explaining the development of the movement over the past six years, from mobilization of third-party supporters on behalf of victims to victims’ strong commitment, this article analyses why this movement had only limited success. It is argued that (1) the absence of litigation and early access to officials hampered mobilization of other victims and third-party supporters; (2) bureaucratic conciliatory measures and the victims’ faith in the government’s benevolence limited political opportunities for the victims; and that (3) the framing process of the victims’ movement encountered severe difficulties in developing shared collective identities of the victims and facilitating rights assertions by the victims.<br
Keywords: voluntary evacueesFukushimanuclear disastersocial movementvictims’ movement

Civil society involvement in the policy-making after Fukushima: The Case of the Nuclear Disaster Victims’ Support Law - Löschke, Ayaka (Social Movements and Political Activism in Contemporary Japan: Re-emerging from Invisibility, 2018)
This chapter examines whether the advocacy of Japan’s civil society has changed after Fukushima, focusing on the policymaking process of the Nuclear Disaster Victims’ Support Law that took place in the period from April 2011 to June 2012. There are two main reasons why this law deserves attention. First, it is one of the few cases of so-called Diet Member bills which were submitted by multipartisan politicians and differ fundamentally from most of Japanese bills drafted by bureaucrats and submitted by the cabinet. Second, its policymaking process showed successful advocacy of civil society organisations (CSOs), more specifically, increased CSO involvement in policymaking after Fukushima with respect to the following six aspects: (1) establishment and expansion of a CSOs’ network, (2) CSOs’ attempts to ensure the transparency of policymaking processes, (3) CSOs’ role as an intermediary between nuclear disaster victims and policymakers, (4) CSOs’ emphasis on the illegitimacy or legitimacy of national policies, (5) CSOs’ demands for accountability from policymakers, and (6) CSOs’ roles as sources of skills and expertise. The examination is mainly based on primary sources, such as protocols of the Diet sessions and documents published by ministries and politicians, as well as on interviews conducted with CSOs and politicians.<br
Keywords: advocacy; civil society; Fukushima; nuclear disaster; policymaking

Die Regulation von Hate Speech unter Abe - Löschke, Ayaka; Kim, Sangyun (Japan 2022: Politik, Wirtschaft und Gesellschaft, 2022)
Das Phänomen der »Hate Speech« gehört zu den wichtigsten Sozialproblemen, mit denen die japanische Gesellschaft sich auseinandersetzen muss. Die japanischen Massenmedien haben im Jahr 2013 begonnen, über rechtsradikale Demonstrationen zu berichten. Seitdem richten sich sowohl die öffentliche als auch die wissenschaftliche Aufmerksamkeit auf Aktivisten, die zuerst im Internet politisch aktiv werden und anschließend an rechtsradikalen Demonstrationen teilnehmen, insbesondere Mitglieder von Zaitokukai (einer sogenannten »Bürgerinitiative gegen Sonderprivilegien für die koreanische Minderheit«). Die Regulierung von Hate Speech in Japan ist ebenfalls auf internationales Interesse gestoßen, denn die Zahl der rechtsradikalen Demonstrationen in Japan ist in den vergangenen Jahren stark zurückgegangen. Dieser Beitrag erklärt zuerst kurz das Hate Speech Gesetz 2016 und dessen Implementierung. Der Hauptteil erklärt, welche politischen Akteure unter der Abe-Regierung besonders zur Regulierung von Hate Speech beigetragen haben. Abschließend weisen wir auf die aktuelle Lage während der Pandemie und die mögliche Gefahr hin, dass das Hate Speech Gesetz nicht ausreichen könnte, um die seit dem Jahr 2021 zunehmende Hasskriminalität zu regulieren. Weil bereits einige englischsprachige Aufsätze wie Higuchi (2020) ausführlich den politischen Entscheidungsprozess rekonstruieren, geht der Hauptteil dieses Beitrags aufgrund unserer eigenen Quellen (Teilnahmebeobachtungen und qualitative Interviews) eher auf einige wichtige Punkte ein, die nicht immer akzentuiert werden. Wir betonen insbesondere, dass weder das Kabinett noch das zuständige Ministerium (Justizministerium), sondern eher ein parlamentarischer Ausschuss (der Rechtsausschuss des Oberhauses) und dessen parteiübergreifenden Mitglieder eine wichtige Rolle bei der Gesetzgebung gespielt haben, und dass Kōmeitō, der langjährige Koalitionspartner der Liberaldemokratischen Partei (LDP), sich sehr aktiv an der Politik gegen Hate Speech beteiligt ha
Keywords: Hassrede; das Hate Speech Gesetz 2016; Regulierung; Kōmeitō

Ironic connectivity and gamification: Keys to online activism against hate speech in Japan - Löschke, Ayaka (12th Annual Nordic NIAS Council Conference “Digital Asia: Cultural, Socio-Economic, and Political Transformations”, 2019)
Japanese counter-protesters against extreme far-right activism launched the new social movement “ban festivals on Japanese Internet right-wing activists” (netouyo ban matsuri) to tighten private censorship in cooperation with Internet Service Providers (ISP) in May 2018. The participants have systematically reported online content to ISPs which could be regarded as in violation of their guidelines. As a result, 640,000 videos and 2150 channels have been removed from YouTube and 69 Mio. tweets and 3300 accounts have been deleted on Twitter as of May 2019. Who did participate in the movement and show short-term and long-term leadership? How does this new activism differ from conventional leftist movements in post-war Japan? My presentation addresses these questions. Taking a “small data” approach, I conducted an analysis of 3345 individual tweets with the hash tags “spring ban festival” and “winter ban festival” that were posted during two weeks at the movements’ peak. I examined not only the text of the tweets, but also images and websites which were attached to the main part of the tweets. I also took account of the meaning of tweets that include Internet slang as well as possible. This presentation suggests that the ban festivals have been successful and differ from conventional leftists movements, because the participants have placed emphasis not on social justice or other leftists ideologies, but on their own amusement and connectivity through a sense of ironical humor. The amusement resembles that which Internet users find in an online fire storm. However, it should be added that the leadership within the ban festivals shifted from such pleasure-oriented non-political users to a small number of online leftists in six months.

Mothers against Radiation: Effort to become a ‘professional’ organization and its failure - Löschke, Ayaka (2021 Annual Conference of the German Association for Social Science Research on Japan “Continuity and Change 10 years after 3.11”, 2021)
Immediately after Fukushima, many mothers became politically active to protect children from radiation, more specifically to abolish the 20 mSv criterion, the annual radiation exposure limit that was raised by the government twentyfold immediately after Fukushima. While most of them failed to keep their engagement around 2015, the Kodomo-tachi wo Hōshanō kara Mamoru Zenkoku Nettowāku (the National Network of Parents to Protect Children from Radiation; the “Kodomozenkoku”) maintained their engagement. Since its establishment in July 2011, more than 340 local groups against radiation from all over Japan joined the Kodomozenkoku as rank-and-file members. The Kodomozenkoku held study groups to warn the public about health risks from low-level radiation exposure in the Tokyo metropolitan area until 2020. Why could the Kodomozenkoku survive for ten years? Why did the Kodomozenkoku fail to keep its advocacy? To examine changes in the Japanese civil society after Fukushima, this article analyzes changes in mothers’ advocacy and organization, using the Kodomozenkoku as a case study, within the framework offered by organizational theory and social movement theory. It focuses on the advocacy, internal structuration, and interorganizational relations that the Kodomozenkoku has undergone for ten years. The Kodomozenkoku was converted from a loose tied volunteer group to a well-organized, centralized Non-Profit Organization (NPO) in 2014. But the Kodomozenkoku shifted its focus from advocacy to non-advocacy activities in spite of a broadened source base and improved decision-making structure. This research is based mainly on the results from 63 qualitative interviews that were conducted between 2013 and 2017. The government policy change regarding radiation in 2013 is not the only reason for the decline of the Kodomozenkoku’s advocacy. This research argues that the Kodomozenkoku’s dependence on other prominent activists, in particular its tendency not to leap into the spotlight as activists in public events, but rather to play a supporting role as a moderator or facilitator also caused a decline in attraction as a political actor.<br
Keywords: Fukushima; advocacy; social movement; organization; NPO

MY NUCLEAR NIGHTMARE: Leading Japan through the Fukushima Disaster to a Nuclear-Free Future | By Naoto Kan; translated from the Japanese by Jeffrey S. Irish - Löschke, Ayaka (Pacific Affairs, 2018)
Voluminous literature on the Fukushima nuclear disaster has been published, but My Nuclear Nightmare: Leading Japan through the Fukushima Disaster to a Nuclear-Free Future might be one of the most important primary sources to be translated into English. The Japanese version was published in 2012. The book is interesting in many research contexts. Scholars who are interested in crisis management, risk communication, the prime minister’s political leadership, media coverage of the prime minister, nuclear regulatory authority, renewable energy policy, and ethical issues such as the lives of nuclear power plant workers, will find the book engaging. Kan’s statements either correspond or relate to other primary sources, such as the report of the National Diet of Japan’s Fukushima Nuclear Accident Independent Investigation Commission; books published by other politicians, such as Fukuyama Tetsurō; or the testimony of the plant manager Yoshida. To examine Kan’s statements, researchers should compare them with these other primary sources. <br
Keywords: nuclear disaster; Fukushima; prime minister

# Neto-uyo BAN Matsuri since 2018: content moderation and user engagement against hateful contents - Löschke, Ayaka (17th International Conference of the European Association for Japanese Studies (EAJS), 2023)
While people spent more and more time on social media during the recent pandemic, hateful content including comments and videos have posed a growing threat in the world. How did online platforms remove or fail to remove hateful content? Because major social media platforms including YouTube and Twitter have struggled with financial losses in recent years, they began to lay off 30-50% of employees including content moderators in November 2022. It is possible that online platforms will increase the number of content moderators also in Japan. In contrast to Germany, Japan did not adopt a legislation to obligate online platforms to remove hateful content within a specific time frame. Therefore, victims of hateful content must spend much time and money to identify and to sue its authors or uploaders. User engagement against hateful content has received international scholarly attention in recent years, because such user engagement is an increasingly indispensable part of content moderation (Gillespie 2018). Users can collectively and systematically report hateful content that could be regarded as violating the platform guidelines to support commercial moderators in detecting hateful content quickly and accurately. Especially a German case study prompted scholars to theorize about determinants of such user engagement (Porten-Cheé et al. 2020; Ziegele & Naab 2020 etc.). How did Japanese users cope with hateful content? To answer the question, my presentation analyzes the “Neto-uyo BAN Matsuri” (Internet Rightists Ban Festival), an online activism which has reported hateful content on YouTube and Twitter since 2018. It shows the main targets of this activism such as right-wing publicists and entrepreneurs who make full use of traditional and new media and identifies the determinants of the user engagement, based on a qualitative analysis of 3,821 tweets and classification of 1,038 participant
Keywords: media industries; hate speech; user engagement

Opening spaces of hope for minorities? Victims’ movements (tōjisha undō) and legislation - Löschke, Ayaka (The 16th EAJS (European Association for Japanese Studies) International Conference, 2021)
‘Tōjisha’ (directly affected people), usually referred to as ‘victims’ in the English-language literature, have been recognized as key players in Japan’s social movements, because they have often influenced the government policy (Upham 1987; Feldman 2000; Arrington 2016). The term has a wide application and includes minority people who are ill-treated by government policy or are suffering from discrimination. It refers not to victims passively awaiting relief but to committed victims who are seeking redress for damage including policy change on their own initiative. My presentation discusses whether and how victims’ movements (Tōjisha undō) open a space of hope for minorities by legislative means, more specifically, ‘principle laws’ (rinenhō). ‘Principle laws’ tend to consist of few articles, introduce no specific penalty, get almost no budget, and explain only basic principles in relatively abstract terms. Based on his analysis of the recent burakumin’s movement and a principle law which was introduced in response to the movement, Bondy (2019) argued that principle laws and their implementation rely exclusively on administrative guidance with no binding force and therefore remain weak and symbolically only. In contrast to his research, my presentation will show the potential of administrative guidance, using the Hate Speech Law of 2016 and its implementation as a case study. Since the Hate Speech Law was enacted in 2016, far-right protests have been rapidly decreasing. I argue that victims can hope that a principle law can have considerable impact if it is implemented in accordance with Japan’s ‘soft’ method of conflict resolution: Japan has historically implemented administrative measures not to directly ban but discourage social activities that are deemed harmful to the value of social harmony.<br

Radiation moms’ organizational survival for a decade: A shift from advocacy to non-advocacy activities - Löschke, Ayaka (Contemporary Japan, 2022)
This article examines changes in Japan’s social movement organizations (SMOs) after the Fukushima Daiichi nuclear disaster, focusing on mothers against radiation as key actors. After the Fukushima disaster, Japan’s SMOs enjoyed not only a resurgence of mass protests, but also an increase in advocacy activities and mothers’ participation in relation to radiation protection. Furthermore, some mothers’ SMOs against radiation survived for a decade. Such longevity is internationally unusual for an SMO. However, these SMOs have been virtually unstudied with regards to this longevity. How did mothers’ SMOs against radiation fight for survival for more than a decade? To answer this question, this project conducted long-term ethnographic research on a mothers’ SMO, the Kodomo-tachi o Hōshanō kara Mamoru Zenkoku Nettowāku (the National Network of Parents to Protect Children from Radiation; the “Kodomozenkoku”). Founded in 2011, Kodomozenkoku has been active for more than a decade. It recruited over 350 local SMOs as rank-and-file and shifted its focus from national advocacy activities to local non-advocacy activities. Based on this case study of Kodomozenkoku, this research argues that Kodomozenkoku’s flexibility in its transformation concerning goals, internal structure and interorganizational relations enabled this newcomer SMO to survive for over a decade.<br
Keywords: Fukushima; social movement; civil society; mothers; advocacy; organizational transformation

Reviews: Foljanty-Jost, Gesine / Hüstebeck, Momoyo (Hrsg.): Bürger und Staat in Japan. - Löschke, Ayaka (Asiatische Studien - Études Asiatiques, 2014)
Der von Gesine Foljanty-Jost und Momoyo Hüstebeck in der Reihe Schriften des Zentrums für Interdisziplinäre Regionalstudien herausgegebene Band ist ein wichtiger Beitrag zur Erforschung der Zivilgesellschaft und der Öffentlichkeit in Japan. Die Beiträge des Bandes sind das Ergebnis von Vorträgen und Diskussionen, die zum Thema „Bürger und Staat“ im Rahmen des Internationalen Graduiertenkollegs „Formenwandel der Bürgergesellschaft“ an der Martin-Luther-Universität Halle-Wittenberg stattgefunden haben. Leser erhalten nicht nur einen profunden Überblick über spezifische Eigenschaften der gegenwärtigen japanischen Zivilgesellschaft, sondern können auch gut nachvollziehen, wie sich eine Konzeption von Zivilgesellschaft in Japan historisch entwickelt ha
Keywords: Zivilgesellschaft; Öffentlichkeit; Japan

The national advocacy of Japan’s civil society organizations against radiation: Policymaking and organizational transformation over six years - Löschke, Ayaka (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

The social movement against hate speech for a decade: Legacies from other movements and new strategies - Löschke, Ayaka (British Association for Japanese Studies (BAJS) Conference 2022, 2022)
While the regulation of hate speech has been one of the most important social issues for the last decade in Japan, one of the most important factors which has contributed to the decline of far-right activism, the social movement against hate speech, has not been sufficiently investigated. Shaw (2019, 2020) examines the Japanese Antifa activists, focusing on their relations to the New Left movements that had been established since the 1970s, and their (sub-) cultural backgrounds. Hatano (2021) explains how the understanding of international law reinforced the social movement against hate speech. Higuchi (2020) investigates into the policy-making process of the 2016 Hate Speech Law to which the participants in the movement against hate speech have contributed significantly. However, no scholar has yet asked why the social movement against hate speech could keep its strength for a decade in spite of the fact that most of the participants did not aim for organizational maintenance. Based on the results from 70 interviews which were conducted mainly in Shinjuku, Kawasaki, Kyoto, and Osaka between 2016 and 2021, this presentation analyzes the movement against hate speech, focusing on 1) personal ties, 2) financial power, and 3) access to local and national politicians. I argue that this movement is a crystallization of legacies from different social movements which include not only the Post-Fukushima anti-nuclear movement, but also the movement for local foreign suffrage in Kawasaki and the Buraku liberation movement. Moreover, this presentation points out that the movement’s strategy to lobby not only the opposition, but also politicians from the ruling party differs significantly from Post-war social movements in Japa

User Engagement against Online Far-Right Actions in Japan: Driven by High Perceptions of Personal Abilities and Benefits - Löschke, Ayaka (Digital Asia, 2022)
This article presents a case study of user engagement against incivility online in Japan, considering three determinants of such engagement identified in a German case study. Japanese users launched the #Internet Rightists Ban Festival in 2018 and are continuing their engagement. As a result, more than 10,500 Twitter accounts have been permanently banned. What drove the participants to initiate and continue their engagement? What type of users attended the festival and led it? This article asks these questions, conducting an inductive qualitative analysis of 3,821 tweets and distinguishing 1,038 participants. It argues that Japanese user engagement has been driven in particular by the perception of personal abilities, such as gaming and comment-writing skills, and the perception of personal benefits, especially from gamification and irony. This article also identifies participants’ left-wing political orientation as an important factor in their continuing sense of responsibility and leadershi
Keywords: flagging; gamification; hate speech; incivility online; irony; Japan; playfulness; user engagement

User engagement against online hate speech in Japan: Driven by high perceptions of personal abilities and benefits - Löschke, Ayaka (Conference “Diverse Approaches to Hate Speech: debates, Challenges, and Controversies”, 2022)
User engagement against online hate speech has supplemented professional content moderation and constitutes an increasingly indispensable part of content moderation. Considering three determinants of user engagement against online hate speech that were identified in a German case study, this research conducts a Japanese case study. Japanese users launched the #Internet Rightists Ban Festival in 2018 and are continuing their engagement. As a result, about 963,000 videos and 3,900 channels have been removed from YouTube About 250 million tweets and 11,000 accounts have been deleted from Twitter. The YouTube channels and Twitter accounts of prominent right-wing publicists have also been permanently or temporarily banned. What drove the participants to carry out and maintain their engagement? What type of users attended the festival and took the leadership? This research asks these questions, conducting an inductive qualitative analysis of 3,821 tweets and classifying 1,038 participants. The sample was selected from tweets that were posted during three different periods between 2018 and 2020. It is argued that the Japanese user engagement has been driven especially by the perception of personal abilities, such as gaming and comment-writing skills, and the perception of personal benefits, especially from gamification and irony. This research also identifies participants’ left-wing political orientation as an important factor in keeping a sense of responsibility and taking leadershi
Keywords: online activism; Japan; incivility online; hate speech; irony; gamification

Working customers against online hate speech: Driven by high perceptions of personal abilities and benefits - Löschke, Ayaka (International Workshop “East Asia in the Digital Age: Digital Transformation in Technological, Economic and Social Perspective, 2022)
Social media platforms are available free of charge in exchange for users’ free labor such as watching advertisements. While such labor has increased recently, some social media users even started to report systematically online hate speech to internet service providers in democratic countries. What, for example, drove Twitter users to carry out and maintain their engagement? Using a theoretical framework offered by a German case study, this research conducts a Japanese case study and shows results of inductive qualitative analysis of classifying 1,038 participants in the #Internet Rightists Ban Festival launched in 2018 and their 3,821 tweets. It is argued that the Japanese user engagement has been driven especially by the perception of personal abilities, such as gaming and comment-writing skills, and the perception of personal benefits, especially from gamification and irony.<br

住宅支援打ち切りへの抗議: ―自主避難者による抗議運動の成否を分けた六つの要因 (Jūtaku shien uchikiri e no kōgi: Jishu hinansha ni yoru kōgi undō no seihi wo waketa 6-tsu no yōin) - Löschke, Ayaka (福島原発事故被災者 苦難と希望の人類学―分断と対立を乗り越えるために, 2022)
福島第一原発事故発生から数ヶ月後、「自主避難者」という新たな用語が作られた。自主避難者とは、3.11後、政府による避難指示が出なかった地域から避難した人びとを指す。 多くの自主避難者は東京電力による補償を受けられず、補償を受けられたとしても、ごくわずかな補償額しか受け取ることができなかった。東電による補償とは別に、政府は自主避難者に住宅を無償提供するために年間八〇億円を拠出した。大半の住民たちには避難先で民間の賃貸住宅を借りるだけの十分な財力がなかったので、この住宅政策は住民たちにとって「命綱」であり続けた。本章は、こうした住宅支援打ち切りに抗議するために形成された自主避難者の当事者運動を分析する。 この運動はいかにして生じ、いかなる変容を見せていったのか。自主避難者のうち、いかなる人びとが運動に参加したのか。この運動はなぜ、限定的な成功しか収めることができず、政府による住宅支援打ち切りの決定を覆すことができなかったのか。本章は、一九八〇年代以降、日本社会を研究する法学者・社会学者・政治学者たちから国際的に注目され、二〇一六年以降、再び脚光を浴び始めている社会運動の一形態、「当事者運動」の研究を背景として、これらの問いに一定の答えを出すことを試みる。 本研究は、二〇一四年一〜二月、二〇一五年一一月におこなわれたフィールドワーク、そして、インターネットを通じて継続的におこなわれたエスノグラフィーの結果に基づいている。質的インタビュー調査の対象となったのは、二一人の自主避難者と、四〇人の支援者であ
Keywords: voluntary evacuees; Fukushima; nuclear disaster; social movement; victims’ movement

行政によるヘイトデモ規制: 日本型の社会統制の一例として - Löschke, Ayaka (Shakai kagaku kenkyu (The Journal of Social Science), 2023)
極右活動家によるヘイトスピーチを伴うデモ，いわゆる「ヘイトデモ」を規制するために行政がとる予防的措置，抑止策は日本で大きな効果を上げている．国の法律はヘイトスピーチに刑罰を科していないものの, 日本においてヘイトデモは急速に減少している．日本におけるヘイトデモ規制はなぜ，そのような効果をもたらしたのか．日本におけるヘイトスピーチ規制は主に法学分野で論じられているが，日本の行政がヘイトデモを規制するために様々な措置を講じてきたことはあまり注目されていない．よって本稿は，ヘイトスピーチ解消法（2016 年）の施行に焦点を当て，極右活動家に対する行政の対応を，強制力を行使せず，いわば「ソフトな」方法を用いる日本型の社会統制の一例として検討する．日本型の社会統制とは，「社会の和」を乱すと思われる活動を直接禁止するのではなく，そうした活動を企てる人々を萎縮させたり，思い止まるよう説得したりして，抑止しようとするものである．ヘイトデモを規制するための措置も，そうした抑止策が中心で，公共空間で許容される言動に関して都道府県警察，地方公務員，極右活動家が事前に一定の合意を形成することによって実施される．本稿は，極右活動家と，路上でヘイトスピーチに反対する「カウンター」行動参加者双方への日本社会の対応が，「社会の和」の概念と同根の概念である「喧嘩両成敗」の原則に基づくことも明らかにする．喧嘩両成敗とは，喧嘩の原因や正否を問わず，当事者双方を処罰するという原則である．ゆえに，日本におけるヘイトデモへの対処の仕方は，規制の方法と，その根底にある価値概念の観点から見て，従来のアメリカ型の規制ともヨーロッパ型的規制とも異な
Keywords: ヘイトスピーチ，ヘイトデモ，極右活動家，行政指導，社会の和